PERBANDINGAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK SEBELUM DAN SESUDAH BEGADANG PADA SECURITY DI PERUMAHAN J-CITY MEDAN JOHOR - Siska Anggreni Lubis; Muhammad Amin (Jurnal Penelitian Keperawatan Medik, 2018)
Blood pressure is the pressure generated by the blood against the blood vessel. Staying up late isbeing awake until late at night. All the human need a time for rest, a normal adult requires six toeight hours a day sleeping or resting after a day of working and doing activity.The purpose ofthis research was to compare the systolic and diastolic blood pressure before and after stayingup on security in Perumhan J-City Medan Johor. This observational analytical research is crosssectional design in use with a sample of 43 securities with sampling methods Total Sampling. Theresults showed that 43 respondents who examined contained blood pressure increased by 32(74%) of people, who decreased as many as 8 (18,6%) people, and being consistent 3 (7%) ofpeople.Paired T-test based on the obtained on the average systolic pressure before and after is -8.140. The result of this study relateds to the significance of p=0,001. For the average diastolebefore and after obtained -6.744 which also relates to the signifance of p= 0,001.